Miraculous movements : how hundreds of thousands of Muslims are falling in love with Jesus - Trousdale, Jerry (Nashville : Thomas Nelson, 2012)
"Miraculous Movements recounts an amazing change taking place within Muslim communities where the truth of Jesus Christ is turning around the lives of many thousands of Muslims. This close look at what the Lord is doing to spread the gospel highlights the key scriptural principles that help Christians reach out in love to share the gospel in their own community. The author outlines the principle of service to others that will open the doors of opportunity to the work of the gospel."--Publisher's description.
Unprecedented! -- Jesus' counterintuitive disciple-making strategy -- Pray the Lord of the harvest -- Inside Islam: disillusionment and discontentment -- Engaging lostness -- Discovery Bible studies and obedience-based discipleship -- Simple churches, dramatic transformation, rapid replication -- Dreams, visions, and miracles among Muslims -- "Of whom the world is not worthy": Learning from heroes and heroines of faith -- The hardest people yield the greatest results -- Ordinary people achieving the impossible -- Seven paradigm shifts -- Getting Started-Biblical practices for engaging lostness.
"CityTeam International."
Includes bibliographical references (pages 207-208).
Keywords: Christian converts from Islam